Hypericum hircinum L. components as new single‐molecule inhibitors of both HIV‐1 reverse transcriptase‐associated DNA polymerase and ribonuclease H activities. Issue 3 (2nd July 2013) - Esposito, Francesca; Sanna, Cinzia; Del Vecchio, Claudia; Cannas, Valeria; Venditti, Alessandro; Corona, Angela; Bianco, Armandodoriano; Serrilli, Anna M.; Guarcini, Laura; Parolin, Cristina; Ballero, Mauro; Tramontano, Enzo
Abstract: Among HIV‐1 reverse transcriptase (RT)‐associated functions, DNA polymerase and Ribonuclease H (RNase H) are both essential for HIV replication and excellent targets for drug development. While all RT inhibitors approved for therapy target the DNA polymerase activity, there is the pressing need for new RT inhibitors possibly targeting the RNase H function. In the last 20 years, many natural substances have shown antiviral activity against HIV‐1, but only a few against the RNase H function. In this study, we have tested the ethanolic extracts obtained by the Hypericum hircinum L. ( Hypericaceae ) growing in Sardinia (Italy) on the HIV‐1 RT‐associated RNase H function and found that they have inhibitory effects. Active extracts were fractionated up to obtain the main components that have been isolated, tested, and identified to be betulinic acid, shikimic acid, chlorogenic acid, quercetin, 5, 7, 3′, 5′‐tetrahydroxyflavanone, and 5, 7, 3′, 5′‐tetrahydroxyflavanone 7‐O‐glucoside. Betulinic acid and 5, 7, 3′, 5′‐tetrahydroxyflavanone 7‐O‐glucoside were active on both RT‐associated activities, and betulinic acid was also active on HIV‐1 mutant RTs resistant to efavirenz. Overall, our results suggest that some of these compounds inhibit the HIV‐1 RT binding to an allosteric site previously described for other natural compounds and are potential leads for further drug development of a single molecules having dual inhibitory activity. Abstract : Combination antiretroviral therapy has forever changed the outcome of AIDS, transforming it from an untreatable, fatal syndrome into a manageable chronic condition. However, the search for new therapeutic targets is always on, because of the issue of mutation in the virus determining resistance to all drugs in use. Esposito et al . describe the activities of compounds that they tested against RNase H, a viral enzyme that has not been fully exploited as a target for antiretrovirals. Their results will be relevant to the development of new drugs to treat HIV infection.